2020
DOI: 10.1111/ijcp.13856
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of COVID‐19 Treatment containing both Hydroxychloroquine and Azithromycin: A natural clinical trial

Abstract: The goal of this study was to assess the clinical effectiveness and safety profile of the COVID‐19 treatment protocol (containing both hydroxychloroquine (HCQ) and azithromycin) in an Iraqi specialised hospital. Methods This prospective study used a pre‐ and post‐intervention design without a comparison group. The intervention was routine Ministry of Health (MOH) approved the management of COVID‐19 for all patients. The study was conducted in a public healthcare setting in Baghdad, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…Alternatively, several other well-documented side effects of HCQ might also potentiate the risk of developing neuropsychiatric AEs, particularly SI/SB. For instance, (ii) HCQ treatment can cause hypoglycemia [ 42 ], which could trigger dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis, and, subsequently, cortisol rhythm [ 43 , 44 ] ( Figure 1 ). Notably, alterations in these signaling pathways have been associated with increased suicide risk [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, several other well-documented side effects of HCQ might also potentiate the risk of developing neuropsychiatric AEs, particularly SI/SB. For instance, (ii) HCQ treatment can cause hypoglycemia [ 42 ], which could trigger dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis, and, subsequently, cortisol rhythm [ 43 , 44 ] ( Figure 1 ). Notably, alterations in these signaling pathways have been associated with increased suicide risk [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the study had two main limitations: a small sample size (36 patients, of which only six were assigned to receive HCQ-AZM), a limited follow-up, and safety data not sufficiently reported. Likewise, another trial conducted by Abbas et al 47 (2020), involving 161 patients, demonstrated that HCQ-AZM was useful to improve time to resolution of symptoms. However, it was a singlecenter study conducted without a control group.…”
Section: Clinical Trialsmentioning
confidence: 94%
“…A clinical study demonstrated that signs and symptoms of SARS-CoV-2 infection were significantly reduced in response to a treatment regimen containing hydroxychloroquine and azithromycin. The most common side effects reported were stomach pain, hypoglycemia, dizziness, pruritus, rash, and QT prolongation [33]. Another study conducted demonstrated the efficacy of the combination of hydroxychloroquine and azithromycin on both viral clearance and shorter hospitalization time for COVID-19 patients [34].…”
Section: Clinical Efficacymentioning
confidence: 99%